2016
DOI: 10.4174/astr.2016.91.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Two-port laparoscopic appendectomy assisted with needle grasper comparison with conventional laparoscopic appendectomy

Abstract: PurposeThe 2-port laparoscopic appendectomy technique (TLA) is between the conventional 3-port and single-port laparoscopic appendectomy surgeries. We compared postoperative pain and cosmetic results after TLA with conventional laparoscopic appendectomy (CLA) by a 3-port device.MethodsPatients undergoing TLA were matched with patients undergoing CLA between February 2015 and November 2015 at the same institution. Thirty-two patients underwent TLA with a needle grasper. The appendix was secured by a percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…When Donmez et al . introduced a needle grasper device at McBurney's point to hold the appendix, the procedure took 57.03 min . These findings indicate that DILA is comparable and equivalent to CLA in terms of duration of surgery.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…When Donmez et al . introduced a needle grasper device at McBurney's point to hold the appendix, the procedure took 57.03 min . These findings indicate that DILA is comparable and equivalent to CLA in terms of duration of surgery.…”
Section: Discussionmentioning
confidence: 71%
“…In the first 6 h after surgery in this study, the mean postoperative pain was 6.5 ± 1.4 in the CLA group and 6.4 ± 1.2 in the DILA group; in contrast, Donmez et al . found that the mean postoperative pain was 4.37 in the CLA group and 4.25 in the DILA group . The mean postoperative pain after 24 h was 4.3 ± 1.8 in the CLA group and 4.1 ± 1.9 in the DILA group.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the literature, many methods such as classical laparoscopic appendectomy, single port, two ports, Natural Orifice Transluminal Endoscopic Surgery (NOTES) have been described so far. (3)(4)(5)(6). In the present article, we aimed to present the laparoscopy-assisted minimally invasive appendectomy using two 5 mm ports.…”
Section: Introductionmentioning
confidence: 99%